Divinity for all persuasions;almanacs and early american religious life. - T. J. Tomlin (Oxford University Press, 2014)
A Divinity for All Persuasions uncovers the prevailing religious sensibility at the center of early America's most popular form of print: the almanac. Employing a wealth of archival material, T.J. Tomlin reveals the pan-Protestant sensibility distributed through the almanacs' pages between 1730 and 1820, finding that almanacs played an unparalleled role in reinforcing British North America's ""shared religious culture.""